EATING HABITS AND BEHAVIOR IN ADOLESCENTS FROM DIFFERENT ETHNIC GROUPS IN THE MUNICIPALITY OF PLOVDIV, BULGARIA - Gergana Petrova; Elena Merdzhanova; Valentina Lalova; Penka Angelova; Nikolay Boyadjiev (Peytchinski Publishing, 2022)
Purpose: The present study aims to analyze eating habits and behavior in adolescents from different ethnic groups in the Municipality of Plovdiv, Bulgaria. Material and methods: This cross-sectional study was carried out with three different ethnic groups (Bulgarian, Turks, and Roma) in Plovdiv Region in Bulgaria. The study was conducted with a total of 185 middle or high school students. For the purposes of the study original semi-structured questionnaire was developed. Statistical analyses were performed using SPSS Statistics v. 26 software (IBM Corp. Released 2019. Armonk, USA). Results: More than half of the respondents eat breakfast in the morning, 107 (57.8%) sometimes eat breakfast, 52 (28.1%), and 26 (14.1%) never eat breakfast. Around 93% (50.3%) of children consume pasta daily, with the highest daily consumption among children of Turkish and Roma origin 21 (40.39%) Bulgarian boys and 14 (31.82%) Bulgarian girls consume pasta among Bulgarian children. More than half of the respondents, 105 (56.8%), consume fruits and vegetables daily. This trend persists among ethnic groups, but we have to note the fact that Roma boys at the age of 13 consume the least fresh fruits and vegetables compared to children from other ethnic groups. Conclusions: More than half of the adolescents surveyed eat breakfast in the morning; Pasta products are consumed daily by half of the respondents, with the highest daily consumption among children of Turkish and Roma origin; Fruits and vegetables are consumed daily by more than half of the respondents.